The Use of Expressions of Self Interjection and its Meaning on Social Media - Wahyuni, Rani Sri; Komara, Mutiara Andayani (Universitas Suryakancana, 2023)
This article will describe various kinds of expressions of teenagers on social media such as Facebook, Instagram, Whatsapp, and others. The method used in this research is a descriptive method with a qualitative approach. The results of the study show that the majority of teenagers in Purwakarta use social media to share experiences through uploaded photos and statuses. Uploading self-expression through social media is carried out every day with high intensity. The expressions used generally function to express surprise or shock, pleasure, anger, sadness, and so on. The most used social media is Facebook. Adolescents' motivation in expressing themselves is due to the desire to express feelings and display personal photos as entertainment and to get responses from others. Their satisfaction is a source of pride in themselves. This satisfaction is generally influenced by the mood of teenagers who usually change. Self-expression for adolescents can also be interpreted as a place for self-existence driven by the desire to be known by many people (viral).Keywords: expression; interjection; social mediaAbstrakÂ Artikel ini akan memaparkan berbagai macam ekspresi para remaja di media sosial seperti Facebook, Instagram, Whatsapp, dan yang lainnya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa mayoritas remaja di Purwakarta menggunakan media sosial untuk berbagi pengalaman melalui foto dan status yang diunggah. Pengunggahan ekspresi diri melalui media sosial dilakukan setiap hari dengan intensitas yang tinggi. Ungkapan yang digunakan pada umumnya berfungsi untuk mengungkapkanÂ Â rasa kaget atau keterkejutan, rasa senang, rasa marah, rasa sedih, dan sebagainya. Media sosial yang paling sering digunakan adalah facebook. Motivasi remaja dalam mengeskpresikan diri karena adanya keinginan untuk mencurahkan perasaan dan menampilkan foto-foto pribadi sebagai hiburan dan agar mendapatkan respon dari orang lain. Kepuasan mereka menjadi kebanggaan terhadap dirinya sendiri. Kepuasan tersebut umumnya dipengaruhi oleh suasana hati remaja yang biasa berubah-ubah. Ekspresi diri bagi remaja bisa dimaknai pula sebagai ajang untuk esksistensi diri didorong oleh keinginan untuk dikenal banyak orang (viral). Kata kunci: ekspresi; interjeksi; media sosial.